KARAKTER ANATOMIS DAN FISIOLOGIS KEDELAI (Glycine max (L.) Merril) ‘GROBOGAN’ HASIL PERLAKUAN KEKERINGAN DAN MULSA JERAMI - CAMBABA, SUNARTI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Soybean plant (Glycine max (L.) Merril) is one of the crop commodities which has been cultivated by Indonesian people as primary source of vegetable protein. The difficulties on cultivating soybean plant especially in dryland are lack of water availability, competition with weeds and insect pests. Straw mulches can be used to reduced ground water evaporation and weeds growth. This research were aimed to know the anatomy and physiology characters of soybean (Glycine max (L.)Merril) 'Grobogan' resulted from drought and straw mulches treatments, and aimed to know mulches thickness and watering level can increased the growth and production of soybean. The design of this experiment was Completely Randomized Design with two factors and three replicates. The first factor was the frequency of watering which consist of ( C0 = watering once in a day, C1 = once in a week and C2 = once in two weeks) and the second factor was straw mulches usage which consist of (M0 = without mulches, M1= 1 cm, M2 = 3 cm, M3 =5 cm). Treatments were done for 60 days. The observed parameters were anatomy parameters (epidermis, korteks thickness and trachea diameter roots and stem